TINJAUAN MANFAAT KOMPOS DAN APLIKASINYA PADA BERBAGAI BIDANG PERTANIAN - Wahyono, Sri (Jurnal Rekayasa Lingkungan)
Application of chemical fertilizer without adding organic mater causing land poor in nutrients and low of microbial diversity. It causes dedradation of land fertility. This situation can be solved by applying of compost. Nevertheless, macronutriens content of compost are low, it has advantages such as improving physical soil properties, soil permeability, porosity, structure, water holding capacity, etc.Compost application effect is depend on the type of plant and physico-chemical properties of soil, compost characteristics, doses and time of compost application. Compost aplication is agronomically and economically benefit for farming activities that is in line with the organic farming.Key words: Compost, fertilizer, agricultural